Optical Fiber Communication Conference 2017
DOI: 10.1364/ofc.2017.w3i.4
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Dynamic Multi-layer Resource Allocation and Optimization in Application-Centric Networking

Abstract: In an SDN-based network, connection requests can be accommodated according to application requirements. We devise a framework where such requirements drive IP and optical network resource allocation, dynamic optimization, and instantiation through an SDN orchestrator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…More recently, a number of studies on lightpath provisioning using SDN have been conducted [52][53][54]. Garrich et al [52] proposed an SDN-based optical network that focused on timesynchronisation operations with an objective to reduce lightpath disruption time.…”
Section: Lightpath Establishment In Sdnmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a number of studies on lightpath provisioning using SDN have been conducted [52][53][54]. Garrich et al [52] proposed an SDN-based optical network that focused on timesynchronisation operations with an objective to reduce lightpath disruption time.…”
Section: Lightpath Establishment In Sdnmentioning
confidence: 99%
“…Garrich et al [52] proposed an SDN-based optical network that focused on timesynchronisation operations with an objective to reduce lightpath disruption time. Matrakidis and co-authors [53] proposed a framework for dynamic multi-layer resource allocation for SDNbased optical networks using lightpath as an application. In some studies [52], it has been shown that lightpath routing cannot be initiated until RWA is completed and relevant resources required for establishing connections are reserved and configured.…”
Section: Lightpath Establishment In Sdnmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same framework with the Net2Plan event generator to generate requests, we run simulations on a test network with realistic application demands [8] showing that our strategy provides reasonable resources for each application class. Periodic re-optimization of the IP routes helps reduce the power consumption of the network without causing service interruptions.…”
Section: A Framework For Application-aware Dynamic Multi-layer Resour...mentioning
confidence: 99%
“…In this paper, we use the framework to show how the application-centric approach can be used to the benefit of both the applications and the service provider. The difference to study 3 is that the orchestrator now interacts more intensively with the application, and that we use network path availability (with respect to component mean times to failure and repair) as the constraining service requirement.…”
Section: Introductionmentioning
confidence: 99%